Tannerella Forsythia is Associated with Increased Levels of Atherogenic low Density Lipoprotein and Total Cholesterol in Chronic Periodontitis (2015)
ABSTRACT: Background: Accumulating evidence suggests that acute and chronic infections with periodontopathogens are associated with an increased risk of cardiovascular disease. The objective of this study was to assess whether Tannerella forsythia and Porphyromonas gingivalis are associated with increased levels of atherogenic low-density lipoprotein (LDL), high-density lipoprotein, total cholesterol (TC), triglycerides and body mass index (BMI) in chronic periodontitis patients. Material and Methods: Medical history and clinical and radiographic examination were conducted in 80 chronic periodontitis patients and 28 healthy individuals. Fasting blood samples were drawn for the measurement of the parameters of dyslipidemia. Anthropometric measurements such as height in meters and weight in kilograms were recorded. Both periodontitis and control subjects were asked to answer a questionnaire with regard to their socio demographic and smoking status. The presence of T. forsythia, and P. gingivalis was detected using primers designed to target the respective 16S rRNA gene sequences. Results: The occurrence of T. forsythia and P. gingivalis was higher in the group of subjects with periodontitis. Superior levels of triglycerides were observed in chronic periodontitis patients compared to healthy individuals. High levels of TC in periodontitis persons were significantly associated with increased bleeding on probing. Greater mean levels of TC and LDL were shown in the presence of T. forsythia (P<0.05). Likewise, higher proportions of patients with BMI ≥25 kg/m2 related with T. forsythia (P<0.05). T. forsythia was a significant discriminating factor in the multivariate linear regression model emerging as significant explanatory of increased levels of TC (β=17,879, 95% CI = 4,357-31,401; p=0.01) and LDL (β=17,162, 95% CI= 4,009-30,316; p=0.01). Conclusions: Higher levels of serum total cholesterol and LDL were observed in the occurrence of T. forsythia and the presence of this periodontopathogen may increase the atherogenic potency of low-density lipoprotein that may augment the risk for atherosclerosis in periodontal disease patients.